Implementation of Contextual Teaching and Learning (CTL) in Akidah Akhlak Subjects for Bullying Prevention at Nusantara Plus Senior High School (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study aims to examine the implementation of Contextual Teaching and Learning (CTL) in the subject of Akidah Akhlak at Nusantara Plus Senior High School, with a particular focus on its role in preventing bullying behavior. The research describes how CTL is applied, analyses its impact, and identifies both supporting and inhibiting factors that influence its effectiveness. A qualitative approach with a case study design was employed. Primary data were collected through in-depth interviews, classroom observations, and documentation involving teachers, students, and school staff. Secondary data were obtained from syllabi, lesson plans, and school reports. Data analysis followed Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that CTL is implemented through seven key components: constructivism, inquiry, questioning, learning communities, modelling, reflection, and authentic assessment. This approach was found to enhance students’ empathy, critical awareness, and preventive behaviour against bullying. Supporting factors include teacher competence, the school’s religious culture, student participation, and adequate facilities. Constraints consist of limited instructional time, varied student readiness, and the lack of contextual learning resources. The results of this study can be applied in Islamic religious education, character education, and secondary school curriculum development as a value-based strategy for bullying prevention. Importantly, the study makes a novel contribution by directly linking CTL implementation in Akidah Akhlak lessons with bullying prevention at the senior high school level, while highlighting behavioural and moral transformation among students, rather than focusing solely on cognitive achievement.